EFFECTS OF DIETARY RECOMBINANT GROWTH HORMONE WITH WATERBORNE CALCIUM CARBONATE SUPPLEMENTATION ON GROWTH PERFORMANCE AND GH–IGF AXIS-RELATED GENE EXPRESSION IN JUVENILE SNAKEHEAD (Channa striata) - Indah Permata Sari; Alimuddin Alimuddin; Agus Oman Sudrajat; Tatag Budiardi (Agency for Marine and Fisheries Extension and Human Resources, 2026)
This study evaluated the effects of dietary recombinant growth hormone (rGH) and waterborne calcium carbonate (CaCO3) supplementation on growth performance, feed utilization, body composition, and growth-related gene expression in snakehead (Channa striata) juveniles. The experiment was conducted for 90 days using four treatments: control (R0C0, without rGH and CaCO3 supplementation), treatment 1 (R5C0, 5 mg kg-1 rGH and without CaCO3 supplementation), treatment 2 (R5C25, rGH and 25 mg L-1 CaCO3 supplementation), and treatment 3 (R5C50 rGH and 50 mg L-1 CaCO3 supplementation), each with six replicates. The results showed that rGH significantly increased final body weight (BWt) and specific growth rate, and reduced feed conversion ratio (FCR) compared with the control. Final body weight was significantly higher in R5C0 and R5C50 than in the control, with no significant difference between these treatments. In contrast, body length increased significantly with increasing CaCO3 dose, with the highest value observed in R5C50. Feed conversion ratio decreased significantly in all rGH treatments but did not differ among R5C0, R5C25, and R5C50. Protein and lipid retention were highest in R5C0 and decreased with CaCO3 supplementation. Body calcium content increased with CaCO3 supplementation, with the highest value observed in R5C50. Gene expression analysis showed that rGH significantly increased GH and IGF-1 expression compared to the control, while no consistent significant differences were observed among combined treatments. These findings suggest that rGH predominantly enhanced weight gain and feed utilization, whereas CaCO3 supplementation under rGH treatment was associated with increased body length. The combined treatments resulted in complementary but parameter-specific effects.